Social determinants of health and diabetes self-care management in South Africa - Assegid Hellebo; Andre Pascal Kengne; Amarech Obse; Naomi Levitt; Bronwyn Myers; Susan Cleary; Olufunke Alaba (BMC, 2024)
Abstract Objective Diabetes is an incapacitating condition affecting millions of people in South Africa. Maintaining optimal glycaemic control is crucial in preventing diabetes complications, highlighting the importance of diabetes self-care. This study examined how Social Determinants of Health (SDoH) are associated with self-care management practices in individuals with diabetes in South Africa using the framework developed by the Healthy People 2020 initiative. Methods This study utilised cross-sectional Project Mind baseline data collected in 2017. Self-care management was coded on a scale from '0' (never) to '7' (daily adherence). For analysis, this scale was dichotomised into two categories: low self-care (scores 0-5) and high self-care (scores 6-7). Furthermore, adherence with these daily self-care activities was categorised into three levels: no adherence, partial adherence (inconsistent or partial adherence to activities), and full adherence (consistent adherence to all self-care activities). Results The analytical sample (n = 539) was predominantly female (76%), with a mean age of 54 years, urban residents (60%), unemployed (70%), and attained secondary education (11.3%). In determining the attainment of a higher scale of self-care, age (AOR = 1.02, CI=[0.99,1.05]) and secondary education (AOR = 1.13, CI=[1.02, 2.03]) were associated with an increase in the scale of self-care. Conversely, urban residency (AOR = 0.50, CI=[0.29,0.88]) and being obese (AOR = 0.43, CI=[0.19,1.00]) were associated with a lower scale of self-care. Although not statistically robust, food insecurity decreased while being a woman and having a stable house showed an increased association. Travelling longer distances to access healthcare was positively associated with no adherence, and urban residency has a negative association with full adherence relative to partial adherence. Conclusions The associations between SDoH and diabetes self-care management within a South African context highlight the need for a more holistic understanding and approach to interventions. Future endeavours should examine these determinants more broadly and formulate integrative strategies to ameliorate diabetes self-care.